2021
DOI: 10.1093/tbm/ibab031
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of peer recovery coach services for opioid overdose patients in emergency departments in Indiana: findings from an informal learning collaborative of stakeholders

Abstract: The Recovery Coach and Peer Support Initiative (RCPSI) in Indiana focused on implementing peer recovery coaches (PRCs) to engage opioid overdose patients in emergency department (ED) settings and promote entry into recovery services. State workers and researchers organized an informal learning collaborative primarily through teleconference meetings with representatives of 11 health service vendors to support implementation. This study presents qualitative analysis of the teleconference meeting discussions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Several of the concerns revealed in our research reflect those that have been previously identified in the literature, including the importance of training of ED personnel about PSWs, clarifying the PSW role in the ED, obtaining buy-in, ensuring the PSW is a good fit, collaboration with a recovery community organization, privacy concerns, and payment/reimbursement [16][17][18][19]24,26,39]. Based on the study results, the authors of this manuscript have provided a checklist (see Table 3) describing the key areas for consideration, to help hospital EDs successfully hire and integrate PSWs.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Several of the concerns revealed in our research reflect those that have been previously identified in the literature, including the importance of training of ED personnel about PSWs, clarifying the PSW role in the ED, obtaining buy-in, ensuring the PSW is a good fit, collaboration with a recovery community organization, privacy concerns, and payment/reimbursement [16][17][18][19]24,26,39]. Based on the study results, the authors of this manuscript have provided a checklist (see Table 3) describing the key areas for consideration, to help hospital EDs successfully hire and integrate PSWs.…”
Section: Discussionmentioning
confidence: 70%
“…Buy-in: For ED directors/managers and staff to buy into the idea of employing a PSW, it is important that they have a full understanding of what PSWs do and how best to integrate them within the ED [39,42]. Research demonstrates that conflicts can arise when staff are not prepared for the inclusion of PSWs [30].…”
Section: Hospital Levelmentioning
confidence: 99%
“…Prior work has demonstrated provider confusion related to 42 CRF Part 2 that is perceived to inhibit communication between providers, and this can in turn negatively impact care coordination [ 46 ]. While not documented in the data represented in this article, discussions from an informal learning collaborative in which RCPSI vendors participated [ 47 ] demonstrated 42 CFR Part 2 was a sticking point of confusion that limited communication between rural and urban hospitals. Fortunately, one of the main urban hospitals to which rural vendors transported patients participated in the collaborative, and they were able to work together to address some of the issues around 42 CFR Part 2.…”
Section: Discussionmentioning
confidence: 99%
“…Peer Support Specialists promote individuals' recovery process (Masih et al 2021;Wayne et al 2019), serve the public good (Magidson et al 2021;Reif et al 2014;Staton et al 2021), and diversify recovery options outside the clinical setting (Kleinman et al 2020). This study is the first of its kind to capture the voices of Peer Support Specialists to: (1) document the experiences of and the motivations to become a Certified Behavioral Health Peer Support Specialist; (2) understand the factors that affect recruitment and retention; (3) offer recommendations for strengthening this resource in Montana from the perspective of Certified Behavioral Health Peer Support Specialists.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on peer support specialists largely focuses on the positive benefits clients gain from peer-to-peer relationships (Masih et al 2021;Wayne et al 2019). Studies show that patients working with peer recovery coaches experience reduced relapse rates, increased treatment retention, improved relationships with treatment providers and social supports, and increased satisfaction with the overall treatment experience (Magidson et al 2021;Reif et al 2014;Staton et al 2021). This study fills a gap in the literature by systematically documenting the experiences of the peers, important because peer support services increase access to treatment for low-income and minority populations by promoting treatment outside the clinical setting (Kleinman et al 2020).…”
Section: Introductionmentioning
confidence: 92%